ATF3-MEDIATED REGULATION OF GENES DIFFERENTIALLY EXPRESSED DURING PHYSICAL ACTIVITY - Naiman, Daiana (Nazarbayev University School of Medicine, 2025)
Previous studies from our laboratory have identified nine genes (ATF3, NR4A2, NFIL3, NR4A3, MAFF, SIK, SLC2A3, MYC, SOCS3) that are differentially expressed between elite athletes and sedentary individuals and suggested their potential interconnection in pathways by using the STRING analysis. As a preliminary step towards revealing the broader gene interaction networks, the current study investigated the ATF3-mediated regulation of SOCS3 expression in the HEK293 cell line. Tamoxifen was applied as a drug that is known to alter the expression level of ATF3. Western blot analysis was conducted to assess protein expression under different conditions. The results demonstrated a dose-dependent increase in ATF3 expression at 2.5 µM and 25.5 µM tamoxifen, suggesting that tamoxifen induces cellular stress, consistent with previous studies. SOCS3 expression was unexpectedly higher in the vehicle control compared to tamoxifen-treated conditions, indicating that tamoxifen’s effect on SOCS3 may be independent of ATF3. Additionally, tamoxifen significantly reduced SOCS3 levels, implying a potential role in regulating cytokine signaling pathways. Further research is necessary to confirm the dosedependent variation between tamoxifen-induced ATF3 gene upregulation and alterations in SOCS3 expression as well as the other remaining genes from the potential pathway network. It will provide a golden opportunity to understand the broader effects of the genes responsible for muscle adaptation in response to physical activity.
Keywords: type of access: open access